Challenges in Physiological Phenotyping of hiPSC-Derived Neurons: From 2D Cultures to 3D Brain Organoids - Mateos-Aparicio, Pedro; Bello, Sabina A.; Rodríguez-Moreno, Antonio (Frontiers in Cell and Developmental Biology, 2020)
hiPSC-derived neurons offer novel opportunities for the development of preclinical models of human neurodegenerative diseases. Recent advances in the past few years have increased substantially the potential of these techniques and have uncovered new challenges that the field is facing. Here, we outline and discuss challenges related to the functional characterization of hiPSC-derived neurons and propose ways to overcome current difficulties. In particular, the enormous variability among studies in the electrical properties of hiPSC-derived neurons and broad differences in cell maturation are factors that impair reproducibility. Furthermore, we discuss how the use of 3D brain organoids are of help in resolving some difficulties posed by 2D cultures. Finally, we elaborate on recent and future advances that may help to overcome the discussed challenges and speed-up progress in the field.